When Journalists and Marketers Negotiate: A Competency-Based Analysis of Negotiation Processes in Brazilian and Belgian Media Organizations - Arraes Moreira, Djenane; Malcorps, Sylvain; Moraes Vitorino, Maíra (Brazilian journalism research, 2019)
This study consists of understanding how interactions between journalists and marketers occur in the context of two organizations from Belgium and Brazil. We seek to understand what is being negotiated, as well as whether there are differences in their applied strategic approaches. To do this, we conducted a cross-national perspective on participant observation and open interviews for data collection. We describe the elements found in the field and relate these processes using “competency-based” analysis. The results of this approach show that issues such as revenue models, organizational cultures, hierarchical positions, relevant professional skills, and personal motives play an important role in the negotiation processes between journalists and marketers. Also, we observe that gatekeeping practices are – to some extent and in specific cases – shared between journalists and marketers. Este estudo consiste em compreender como as interações entre jornalistas e profissionais do marketing ocorrem no contexto de duas organizações da Bélgica e do Brasil. Nosso objetivo é entender o que está sendo negociado, assim como se existem diferenças nas abordagens estratégicas aplicadas. Para tal, nós conduzimos uma perspectiva transnacional com observação participante e entrevistas abertas para coleta de informações. Nós descrevemos os elementos encontrados no campo e os relacionamos a esses processos usando a análise baseada em competências. Os resultados dessa abordagem mostraram questões tais como modelos de negócios, culturas organizacionais, posições hierárquicas, habilidades profissionais relevantes e motivos pessoais, que desempenham um papel importante nos processos de negociação entre jornalistas e profissionais de marketing. Além disso, notamos que as práticas de gatekeeping são – em certa medida e em casos específicos –, compartilhadas entre jornalistas e profissionais de marketing. Este estudio consiste en comprender cómo se producen las interacciones entre periodistas y especialistas en marketing en el contexto de dos organizaciones de Bélgica y Brasil. Nuestro objetivo es entender lo que está siendo negociado, y también si existen diferencias en los enfoques estratégicos aplicados. Para ello, conducimos una perspectiva transnacional con observación participante y entrevistas abiertas para la recolección de información. Describimos los elementos encontrados en el campo y los relacionamos con estos procesos usando el análisis “competency-based”. Los resultados de este enfoque mostraron cuestiones tales como modelos de ingresos, culturas organizacionales, posiciones jerárquicas, habilidades profesionales relevantes y motivos personales desempeñan un papel importante en los procesos de negociación entre periodistas y profesionales de marketing. Además, notamos que las prácticas de gatekeeper son, en cierta medida y en casos específicos, compartidas entre periodistas y profesionales de marketing.